The Effect of Work Environment and Work Stress on Employee Performance: A Quantitative Analysis at Cahaya Pelita Surya - Ardista, Rini; Novialumi, Anita (Jurnal Ilmiah Manajemen Kesatuan, 2023)
The purpose of this study was to determine how motivation work discipline affects employee performance. This research method used in this research is a descriptive quantitative method collecting data from questionnaires from the employees of at CV. Cahaya Pelita Surya in Bekasi, West Java. The software used to process and analyze the data figures is SPSS version 22.0. Based on the results of the analysis and discussion in this study, it can be concluded: there is a positive and significant influence between Work Environment and Work Stress on employee performance variables, this is shown by Work Environment obtained t-table ˃ t-count or (3.119 ˃ 2.048) and Work Stress t-table ˃ t-count (5.845 ˃ 2.048). Based on the results of the f-test, Work Environment and Work Stress simultaneously (simultaneously) have a significant influence on employee performance variables. This is shown by the f-count value of 77.992 which is greater than f-table 3.32 and a significant value of 0.000 which is smaller than 0.05. While the value of the coefficient of determination (Adj R2) is 0.837 which means that the work environment and work stress variables are able to explain the performance variable of 83.7% while the remaining 16.3% is influenced by other factors not included in this study.